Epidemic status in Russia’s Northwestern Federal District: tick-borne encephalitis and ixodes tick-borne borreliosis (lyme disease), 2002–2021 - Islam A. Karmokov; Ekaterina G. Riabiko; Olga V. Blinova; Elena N. Kolosovskaya; Nikolay K. Tokarevich (Russian Journal of Infection and Immunity, 2023)
The study's objective was to reveal trends in tick-borne encephalitis (TBE) and Ixodes tick-borne borreliosis (ITBB) epidemic processes in Russia's Northwestern Federal District (NWFD) in 2002–2021. In the NWFD during the analyzed period, more than 1.1 million patients sought medical help following tick bites (14% of all cases registered nationwide). The long-term average tick bite incidence rate in the NWFD exceeded the nation-wide value: 409.5 and 280.7, respectively. In the NWFD, the highest long-term average tick bite incidence rates were recorded in Vologda Oblast, Pskov Oblast, and Novgorod Oblast. The tick bite incidence rate tended to grow in the NWFD, as well as nationally. The growth in tick bite incidence was statistically significant in the Republic of Komi, Kaliningrad Oblast, and Arkhangelsk Oblast. In 2002–2021, more than 6000 TBE cases were registered in the NWFD (11% of all cases registered nationwide), and the TBE long-term average incidence rate in the NWFD exceeded the national value: 2.3 and 2.0, respectively. The Republic of Karelia, Arkhangelsk Oblast, and Vologda Oblast were three NWFD subjects with high TBE epidemical hazard. TBE incidence in the analyzed period tended to decrease, both in the NWFD and nationwide. A statistically significant decrease in TBE incidence was revealed in St. Petersburg, in the Republic of Karelia, in Novgorod Oblast, and in Leningrad Oblast. About 22 000 ITBB cases were reported in the NWFD during the analyzed period (15% of all ITBB cases in Russia). The ITBB long-term average incidence rate in the NWFD exceeded the national value: 7.9 and 4.9, respectively. Vologda Oblast, Kaliningrad Oblast, and Pskov Oblast were three NWFD subjects with high epidemical hazard in terms of ITBB. ITBB incidence during the analyzed period tended to decrease, both in the NWFD and nationwide. The decrease in ITBB incidence was statistically significant in Vologda, Kaliningrad, Novgorod, Leningrad and Pskov Oblasts, as well as in St. Petersburg. In the Republic of Komi, in ...